Alvaradoins E-N, Antitumor and Cytotoxic Anthracenone C-glycosides from the Leaves of Alvaradoa haitiensis - Phifer, Sharnelle S. (2007)
Bioactivity-directed fractionation of an extract of the leaves of Alvaradoa haitiensis, using the KB (human oral epidermoid carcinoma) cell line, led to the isolation and identification of 10 new anthracenone C-glycosides, alvaradoins E-N (1–10), along with the known compound, chrysophanol (11). The cytotoxicity of all compounds was evaluated, and preliminary structure-activity relationships are suggested. The most potent compounds in the in vitro assays (1 and 2) were evaluated in vivo vs. the P388 (murine lymphocytic leukemia) model, and alvaradoin E (1) showed antileukemic activity (125% T/C) at a dose of 0.2 mg kg(−1) per injection when administered intraperitoneally.